Mapping the cross-border cooperation 'galaxy': an exploration of scalar arrangements in Europe. Issue 12 (2nd December 2022) - Kaucic, Jiannis; Sohn, Christophe
ABSTRACT: The development of cross-border regionalism in Europe has given rise to a multitude of academic works focussing on the pattern, signification and evolution of cross-border cooperation. Most previous studies have, however, focused on individual cross-border cooperation initiatives as units of analysis and neglected their spatial relation to other initiatives. By mapping the perimeter, activity, geographical type, scale and spatial relations of 209 initiatives, the current paper provides an updated and more nuanced overview of the geography of cross-border cooperation in Europe. The cartographic exploration from a rescaling perspective reveals the varying accumulation, scalar focus and activity of cross-border cooperation across Europe and leads to the identification of different forms and evolutions of scalar arrangements constituted by their overlapping perimeters of action. The distinction between nested, overlapping and complex arrangements suggests that different scalar processes are involved in the ongoing structuration of cross-border cooperation, and calls for better consideration of these multi-scalar dynamics in future research.